Analysis of attendees' expenditure patterns to recurring annual events: Examining the joint effects of repeat attendance and travel distance. (February 2015) - Lee, Seul Ki; Sok (Frank) Jee, Won; Funk, Daniel C.; Jordan, Jeremy S.
Abstract: This study examines the changes in expenditure patterns of attendees to recurring annual events, with specific emphasis on the effects of repeat attendance and travel distance. This study utilizes a unique dataset accumulated from six consecutive years at a recurring annual event hosted in Miami, United States. By using the Almost Ideal Demand System (AIDS), we estimate price elasticities and cross-price elasticities among tourist expenditure categories, while jointly examining the effects from the trip characteristics of repeat attendance and travel distance. From the econometric analysis, we find expenditure, own-price, and cross-price elasticities that conform to the literature and confirm the strong inter-relationship among the respective categories of the overall travel budget. In addition, our results confirm a significant difference in expenditure patterns between first time and repeat attendees, as well as between long haul and short haul travelers. Highlights: Relationship of re-visitation and travel distance on tourist expenditure patterns. AIDS framework to estimate price elasticities and cross-price elasticities. Multiyear data to estimate price elasticities of travel expenditures. System of equations approach to examine attendee travel expenditures.